2018
DOI: 10.22159/ajpcr.2018.v11i6.24038
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Phytochemicals and in Vitro Antidiabetic Activity of Bauhinia Racemosa Lam. Leaves

Abstract: Objective: In this study, the leaves of medicinal plant Bauhinia racemosa Lam. with different pharmacological activities were subjected to phytochemical screening and assessment of their in vitro inhibitory potential with porcine pancreatic α-amylase enzyme to treat and management of diabetes.Methods: Plant leaves were extracted sequentially with ethanol solvent. A modified 3,5-dinitrosalicylic acid method was adopted to screen α-amylase inhibition assay. The ethanol extract was analyzed qualitatively and gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Antibacterial activity of the ethanol, methanol, and aqueous extracts was screened by agar well diffusion method as described by Gawade and Farooqui [20] and Abdul et al [21]. Briefly, the bacterial suspension was swabbed uniformly to the Petri dishes containing 20-30 Mueller-Hinton Agar (MHA), and the inoculum was allowed to dry for 5-10 min.…”
Section: In Vitro Antibacterial Bioassaymentioning
confidence: 99%
“…Antibacterial activity of the ethanol, methanol, and aqueous extracts was screened by agar well diffusion method as described by Gawade and Farooqui [20] and Abdul et al [21]. Briefly, the bacterial suspension was swabbed uniformly to the Petri dishes containing 20-30 Mueller-Hinton Agar (MHA), and the inoculum was allowed to dry for 5-10 min.…”
Section: In Vitro Antibacterial Bioassaymentioning
confidence: 99%
“…The major portion of the extract inositol. In a study, GC-MS Bauhinia racemosa leaves revealed inositol and the extract exhibited In-vitro anti-diabetic activity [23].…”
Section: Effect Of Various Treatments On Blood Glucose Level Of Experimental Ratsmentioning
confidence: 98%
“…The extract was preliminary qualitatively analysed for the bioactive phyto-constituents according to the standard protocols [11,12] as…”
Section: Phytochemical Analysismentioning
confidence: 99%